Key financial market concepts : the 100 terms every finance professional needs to know - Steiner, Bob (Pearson, 2011)
"The ultimate reference tool for anyone working in the finance industry, explaining the 100 essential financial market terms. It provides you with a definiton of what each concept is, how it works, when it is likely to arise, how it's calculated and how best to use it. You'll also get access to many of the formulas used, already programmed into a Microsoft Excel spreadsheet, for your own personal use. From the simple and compound interest, through to bonds and yields and the Black and Scholes model, this book has it covered"